Desarrollo e implementación de un sistema de gestión académica y un portal web para el departamento de educación física de la Universidad Nacional de Loja. - Cano Sáenz, Liliana Esther (2010)
Our project "DEVELOPMENT AND IMPLEMENTATION OF A ACADEMIC MANAGEMENT SYSTEM AND A WEB PORTAL FOR THE DEPARTMENT OF PHYSICAL EDUCATION OF LOJA's NATIONAL UNIVERSITY " is clear of two fundamental parts the SISGES (Desktop Application) and the DEFU_WEB (web application). The SISGES allows the processing of information relating to the academic management of the DEFU (University Department of Physical Education) like the ingress and update of the personnel, students, disciplines, schedules, classroom administration, lists printing, certificate and reports, searches of information about the approval, classroom assignment and hourly load of the teachers. The DEFU_WEB is a portal that gives the option to the students to register in certain classroom based on the information about schedules, day and discipline, to consult their assistance percentage and approval of modules. In addition it shows the principal information of DEFU, news about the different events in course and allow to download files previously upload by some member of the personnel. In the theoretical foundation there is described the tools, techniques and methodology used for the development of the project. The Development of the Alternative offer shows the structure of the SISGES and DEFU_WEB across use cases, classes graphs, sequence and screen Prototyping, in addition the results of the validation tests. The Valuation Technique-Operative-Economic make an analysis to determine the feasibility of development of the present thesis project. For the last part is considered the relevant Terms for a better comprehension, there are specified the Conclusions and Recommendations and shows the ANNEXES used in the development of the project.